2010
DOI: 10.1629/23182
|View full text |Cite
|
Sign up to set email alerts
|

Measuring value and return on investment of academic libraries

Abstract: The problem of how to determine the value of a library's services and products is not a new one. Many scholars throughout the years have attempted to take an abstract concept, such as the value of information, and make it more concrete and measurable. 1,2,3,4,5,6,7 What was once often an intellectual exercise, however, now has practical urgency for librarians and for the institutions they serve. This is due both to an uncertain economic climate and to rapid advancements in information technology that call int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…This is often part of an effort to reinforce the importance of the library: for example, Tenopir 11 emphasizes the need to consider measuring the value of libraries, rather than merely marketing them as important, to remind users of what libraries can do for them as a population, and as investors in their costs (be it via taxes for public libraries or tuition fees for academic libraries). Tenopir has more recently been involved in specifically examining academic libraries, 12 surveying faculty to measure the link between citation use, reading, and seeking information with grant-related activities, finding that the library supports key academic research activities and thus can be considered to make a vital contribution to university value. 13 Additionally, Tenopir and Volentine 14 have demonstrated that academic libraries supply extensive resource provisions for materials for their university's research staff, with a particular focus on those who have received rewards or recognition for their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is often part of an effort to reinforce the importance of the library: for example, Tenopir 11 emphasizes the need to consider measuring the value of libraries, rather than merely marketing them as important, to remind users of what libraries can do for them as a population, and as investors in their costs (be it via taxes for public libraries or tuition fees for academic libraries). Tenopir has more recently been involved in specifically examining academic libraries, 12 surveying faculty to measure the link between citation use, reading, and seeking information with grant-related activities, finding that the library supports key academic research activities and thus can be considered to make a vital contribution to university value. 13 Additionally, Tenopir and Volentine 14 have demonstrated that academic libraries supply extensive resource provisions for materials for their university's research staff, with a particular focus on those who have received rewards or recognition for their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, librarians and service providers should take everything possible to improve user satisfaction so that users’ loyalty can be improved (Xu and Du, 2018). Library professionals are looking for new ways to measure and express the value of their libraries to their parent institutions and to measure how well they meet the rapidly changing needs and expectations of their users (Tenopir et al, 2010). “Return on Investment” (ROI) is computed by assessing the statewide value of library material and services to public library patrons and then comparing this value with statewide public library operating expenditures (King, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ROI methodology has been used by academic libraries to try to link the investment (in electronic subscription sources) to gains (in grant income for the universities) on the basis that the successful grant proposals require access to a wide range of information sources to put together a proposal that reflects the current state of evidence on a topic. Various libraries, in a second phase of the ROI study, have tried to use a methodology originally developed at the University of Illinois (Kaufman, 2008;Tenopir et al, 2010), but experience shows that the methodology is not directly transferable (Sidorko, 2010), and much depends on the way the academic libraries are funded, the types of discipline supported (as some disciplines are likely to attract much more research funding than others) and the mission of the university (some are research intensive, others less so). Data collection (collecting data on the successful grant proposals, and combing through the references to identify subscription sources) should be relatively straightforward.…”
Section: Roimentioning
confidence: 99%
“…The meta-analysis included contingent valuation studies as well as ROI studies. Contingent valuation measures the cost in money or time of not having the service, as well as the costs in money or time for having the service (Tenopir et al, 2010). For example, for electronic resources, the question would be how much would it cost to obtain this item if the library did not provide the item through the e-resource collection (and how much time would be involved in obtaining the item).…”
Section: Roimentioning
confidence: 99%